Pakan diameter berbeda bagi pertumbuhan benih sidat (Anguilla sp) - Airin, Dairi Y.L; Lumenta, Cyska (Universitas Sam Ratulangi, 2015)
The objective of research was to establish the effect of different powder diameter on growth, efficiency value and daily consumption of eel seed. This research was conducted at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine Sciences Sam Ratulangi University. Experimental design used was Complete Randomized Design with four treatments, each with three replication. Variables analysed consisted of relative growth, specific growth rate, feed efficiency value and daily comsumption. Results showed that treatment A with poder diameter of 0.125 mm displayed the best relative growth (105.356%), Specific growth (1.29%), feed efficiency value (6,431%), and daily consumption (0.813%). AS conclusion, feed with diameter 0.125 mm was utilized effectively by eel seed. Keywords: relative growth, specific growth rate, feed efficiency value. and daily comsumption, Anguilla sp